Evaluating the Effectiveness of Health Information Systems in Enhancing Disease Surveillance and Reporting in Selected Nigerian States - Olasunkanmi, Owoeye James; Oluwafemi, Egbinade Joshua; Adeleke, Amin Muyiwa; Abayomi O, Ayinde (American Journal of Biology and Natural Sciences, 2025)
Introduction: Health Information Systems (HIS) play a critical role in enhancing disease surveillance and reporting, yet their effectiveness in Nigerian states remains underexplored. Strengthening HIS is essential to detect outbreaks early, guide public health interventions, and improve overall health system performance. Objective: This study evaluated the effectiveness of HIS in strengthening disease surveillance and reporting in Ogun, Osun, and Oyo States, while examining sociodemographic influences and barriers to optimal system use. Method of Analysis: A cross-sectional survey was conducted among 200 health professionals, including Medical Officers and Disease Surveillance and Notification Officers. Data were analyzed using descriptive statistics and chi-square tests to assess relationships between sociodemographic characteristics and perceived HIS effectiveness. Results: The majority of respondents (64.0%) considered HIS tools adequate, 55.0% rated data quality as high, and 60.0% confirmed frequent use of HIS data for decision-making. Significant associations were observed between HIS effectiveness and education level (p = 0.032), designation (p = 0.001), and years of experience (p = 0.017). Major barriers identified were limited funding (69.0%), poor infrastructure (62.0%), and inadequate training (56.0%). Key recommendations included improved funding (78.0%), strengthened ICT infrastructure (74.0%), and regular capacity building (71.0%). Conclusion: HIS are vital for accurate and timely disease surveillance in Nigeria. Addressing barriers through resource investment, workforce training, and policy support will enhance system effectiveness and improve health security.